2001
DOI: 10.1037/0022-006x.69.5.747
|View full text |Cite
|
Sign up to set email alerts
|

Therapists, therapist variables, and cognitive-behavioral therapy outcome in a multicenter trial for panic disorder.

Abstract: The relationship between therapists and treatment outcome was examined in 14 highly trained therapists who participated in the Multicenter Collaborative Study for the Treatment of Panic Disorder. Overall, therapists yielded positive outcomes in their caseloads; yet, therapists significantly differed in the magnitude of change among caseloads. Effect sizes for therapist impact on outcome measures varied from 0% to 18%. Overall experience in conducting psychotherapy was related to outcome on some measures, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
164
2
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 229 publications
(173 citation statements)
references
References 38 publications
4
164
2
3
Order By: Relevance
“…Instruments may differ in their ability to capture important variations in outcome and could therefore lead to different TEs. For example, Huppert et al (2001) analyzed data from the Multicenter Collarborative Study for Treatment of Panic Disorder and found TEs ranging from 1% to 18%, depending on the outcome measure in the field of anxiety disorders. Hence, there may be an impact of instruments on TE sizes.…”
Section: Discussionmentioning
confidence: 99%
“…Instruments may differ in their ability to capture important variations in outcome and could therefore lead to different TEs. For example, Huppert et al (2001) analyzed data from the Multicenter Collarborative Study for Treatment of Panic Disorder and found TEs ranging from 1% to 18%, depending on the outcome measure in the field of anxiety disorders. Hence, there may be an impact of instruments on TE sizes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is also a range of methodological issues that arise when considering therapist effects. In terms of substantive findings, differences in effectiveness between therapists have been reported in some RCTs (e.g., Huppert, Bufka, Barlow, Gorman, & Shear, 2001), while others have reported small or non-significant effects (e.g., Clark et al, 2006;Wilson, Wilfley, Agras, & Bryson, 2011). These conflicting results are exemplified in two independent analyses of the same data, drawn from the National Institute for Mental Health's Treatment of Depression Collaborative Research Project (NIMH TDCRP; Elkin et al, 1989).…”
Section: Therapist Effects: Trials and Routine Practicementioning
confidence: 99%
“…However, any such assumption would be ill-founded, as therapist gender has little consistent impact on therapy performance and patient outcome, with females sometimes performing better than males (Branson, & Shafran, 2015;Huppert, Bufka, Barlow, Gorman, Shear, & Woods, 2001). An alternative explanation is that supervisors might feel that females are more likely to pick up on cues that there are alliance problems, which might stall therapy progression.…”
Section: Supervision For Treatment Of Depression 10mentioning
confidence: 99%